(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2023)
On a numerical example, the application of the method of successive concessions for solving a multicriteria problem of optimizing the design characteristics of a marine cargo ship is considered. The previously developed mathematical model for the design of a ship intended for the carriage of bulk cargo (bulk carrier) was taken as a basis. As optimized variables, the main dimensions, the coefficient of overall completeness and the design travel speed were considered. The purpose of the study was to demonstrate the possibilities of the method of successive concessions in relation to solving ship design problems in a multi-criteria setting, followed by an analysis of the values of partial optimality criteria and optimized variables. Calculations were made for two and four indicators characterizing the functional and economic efficiency of the vessel. It is shown that reaching a compromise is possible by assigning appropriate values of concessions (to a greater extent based on subjective assessments) for particular optimality criteria. Calculations confirm that the smaller the concession, the more stringent the priority of the criterion under consideration and the smaller the change in other indicators under consideration.